A writer's guidebook - Axelrod, Rise B. (St. Martin's Press, 1998)
[This] is a brief reference handbook that offers help with the research and writing you will be asked to do in college and in your career.... It includes guidelines and basic information that will help you plan, research, write, edit, and present any essay or research project. -Introd.